2001
DOI: 10.1161/01.hyp.37.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Increases Endothelial Nitric Oxide Bioavailability by Antioxidative Mechanisms

Abstract: Abstract-Short-term treatment of the endothelium with dihydropyridine calcium antagonists resulted in an increased release in NO that is not due to a modulation of L-type calcium channels, because macrovascular endothelial cells do not express this channel. We investigated whether long-term (48 hours) treatment of porcine endothelial cell cultures with the dihydropyridine calcium antagonist nifedipine resulted in a similar enhanced NO liberation. Regarding to the underlying mechanism, we examined whether (1) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
3
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 55 publications
(53 reference statements)
3
75
3
4
Order By: Relevance
“…This suggests that CR nifedipine may have a beneficial effect on the vascular system beyond its antihypertensive effect. 25,26,[34][35][36] In patients with essential hypertension, platelets appear to be preactivated or hyper-responsive to vasoactive agents. 37 In addition, the activation of platelets contributes to vascular structural changes and the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that CR nifedipine may have a beneficial effect on the vascular system beyond its antihypertensive effect. 25,26,[34][35][36] In patients with essential hypertension, platelets appear to be preactivated or hyper-responsive to vasoactive agents. 37 In addition, the activation of platelets contributes to vascular structural changes and the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that CR nifedipine can improve endothelial function and increase the activity of NO, which regulates platelet activation. 25,26,35,45 It is possible that inhibition of platelet activation improves blood flow in skeletal muscle and thus reduces insulin resistance, resulting in an elevation of circulating adiponectin. 46 The ability of CR nifedipine to inhibit MDMP generation provides additional evidence for the antiatherosclerotic action of this drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,30 Indeed, Iwai et al 17 reported that nifedipine treatment reduced superoxide levels by increasing eNOS activity. However, in our study of eNOS-deficient mice, we found that the nifedipine has eNOS-independent effects on increasing the energy expenditure in skeletal muscle and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Nifedipine treatment reduces atherosclerotic plaques in cholesterol-fed rabbits, 2,3 and suppresses development and progression of atherosclerosis in hypertensive patients. 4,5 Nifedipine has recently been reported to have pleiotropic effects on endothelial cells, 6,7 cardiac muscle cells, 8,9 mesangial cells [10][11][12] and neurons, 13,14 through mechanisms independent of blocking Ca channels. Previous studies have reported that nifedipine treatment decreases body weight in obese hypertensive humans 15 and rat models.…”
Section: Introductionmentioning
confidence: 99%